Time-resolved universal temperature measurements using NaYF4:Er3+,Yb3+ upconverting nanoparticles in an electrospray jet - Shrestha, Kristina; Alaulamie, Arwa A.; Miandashti, Ali Rafiei; Richardson, Hugh H. (Beilstein Journal of Nanotechnology, 2018)
Hexagonal upconverting nanoparticles (UCNPs) of NaYF4:Er3+,Yb3+ (ca. 300 nm) have been widely used to measure the temperature at the nanoscale using luminescence ratio thermometry. However, several factors limit their applications. For example, changes in the peak shape, mainly is the S-band emission, hinders their ability to be used as a universal temperature sensor. Herein, we introduce a universal calibration protocol for NaYF4:Er3+,Yb3+ upconverting nanoparticles that is robust to environmental changes and gives a precise temperature measurement. We used this new procedure to calculate the temperature profile inside a Taylor cone generated with an electrospray jet. Inside the Taylor cone the fluid velocity increases toward the tip of the cone. A constant acquisition length leads to a decrease in excitation and acquisition time. This decrease in excitation time causes a peak shape change that corrupts the temperature measurement if the entire peak shape is integrated in the calibration. Our universal calibration circumvents this problem and can be used for time-resolved applications. The temperature at the end of the Taylor cone increases due to the creation of a whispering gallery mode cavity with 980 nm excitation. We use time-resolved energy balance equations to support our optical temperature measurements inside the Taylor cone. We believe that the findings of this paper provide a foundation for time-resolved temperature measurements using NaYF4:Er3+,Yb3+ upconverting nanoparticles and can be used to understand temperature-dependent reactions such as protein unfolding inside microjet/microdroplets and microfluidic systems.
Keywords: electrospray; microjet; nanothermometry; temperature measurement; time-resolved measurement; upconverting nanoparticles

(untitled) - El-Baba, T. J.; Fuller, D. R.; Woodall, D. W.; Raab, S. A.; Conant, C. R.; Dilger, J. M.; Toker, Y.; Williams, E. R.; Russell, D. H.; Clemmer, D. E. (Chem. Commun., 2018)

(untitled) - Hemmer, E.; Quintanilla, M.; Légaré, F.; Vetrone, F. (Chem. Mater., 2015)

(untitled) - Brites, C. D. S.; Lima, P. P.; Silva, N. J. O.; Millán, A.; Amaral, V. S.; Palacio, F.; Carlos, L. D. (Nanoscale, 2012)

(untitled) - Chen, G.; Yang, C.; Prasad, P. N. (Acc. Chem. Res., 2013)

(untitled) - Rafiei Miandashti, A.; Kordesch, M. E.; Richardson, H. H. (ACS Photonics, 2017)

(untitled) - Rafiei Miandashti, A.; Kordesch, M.; Richardson, H. H. (MRS Adv., 2018)

(untitled) - Richardson, H. H.; Carlson, M. T.; Tandler, P. J.; Hernandez, P.; Govorov, A. O. (Nano Lett., 2009)

(untitled) - Govorov, A. O.; Richardson, H. H. (Nano Today, 2007)

(untitled) - Govorov, A. O.; Zhang, W.; Skeini, T.; Richardson, H.; Lee, J.; Kotov, N. A. (Nanoscale Res. Lett., 2006)

(untitled) - Rohani, S.; Quintanilla, M.; Tuccio, S.; De Angelis, F.; Cantelar, E.; Govorov, A. O.; Razzari, L.; Vetrone, F. (Adv. Opt. Mater., 2015)

(untitled) - Huang, Y.; Rosei, F.; Vetrone, F. (Nanoscale, 2015)

(untitled) - Carlson, M. T.; Khan, A.; Richardson, H. H. (Nano Lett., 2011)

(untitled) - Carlson, M. T.; Green, A. J.; Richardson, H. H. (Nano Lett., 2012)

(untitled) - Carlson, M. T.; Green, A. J.; Khan, A.; Richardson, H. H. (J. Phys. Chem. C, 2012)

(untitled) - Wang, D.; Carlson, M. T.; Richardson, H. H. (ACS Nano, 2011)

(untitled) - Devadas, M. S.; Devkota, T.; Johns, P.; Li, Z.; Lo, S. S.; Yu, K.; Huang, L.; Hartland, G. V. (Nanotechnology, 2015)

(untitled) - Maestro, L. M.; Haro-González, P.; Sánchez-Iglesias, A.; Liz-Marzán, L. M.; García Solé, J.; Jaque, D. (Langmuir, 2014)

(untitled) - Dreaden, E. C.; El-Sayed, M. A. (Acc. Chem. Res., 2012)

(untitled) - Parra-Vasquez, A. N. G.; Oudjedi, L.; Cognet, L.; Lounis, B. (J. Phys. Chem. Lett., 2012)

(untitled) - Carey, C. R.; LeBel, T.; Crisostomo, D.; Giblin, J.; Kuno, M.; Hartland, G. V. (J. Phys. Chem. C, 2010)

(untitled) - Lapotko, D. (Int. J. Heat Mass Transfer, 2009)

(untitled) - Lapotko, D. O.; Zharov, V. P. (Lasers Surg. Med., 2005)

(untitled) - Lapotko, D. (Cytometry, Part A, 2004)

(untitled) - Lapotko, D. O.; Romanovskaya, T. R.; Shnip, A.; Zharov, V. P. (Lasers Surg. Med., 2002)

(untitled) - Lapotko, D. O.; Zharov, V. P.; Romanovskaya, T. R.; Kuchinskii, G. S. (Quantum Electron., 1999)

(untitled) - Lapotko, D.; Romanovskaya, T.; Kutchinsky, G.; Zharov, V. (Cytometry, 1999)

(untitled) - Lapotko, D.; Kuchinsky, G.; Potapnev, M.; Pechkovsky, D. (Cytometry, 1996)

(untitled) - Richardson, H. H.; Thomas, A. C.; Carlson, M. T.; Kordesch, M. E.; Govorov, A. O. (J. Electron. Mater., 2007)

(untitled) - Richardson, H. H.; Hickman, Z. N.; Govorov, A. O.; Thomas, A. C.; Zhang, W.; Kordesch, M. E. (Nano Lett., 2006)

(untitled) - Haro-González, P.; Ramsay, W. T.; Maestro, L. M.; del Rosal, B.; Santacruz-Gomez, K.; del Carmen Iglesias-de la Cruz, M.; Sanz-Rodríguez, F.; Chooi, J. Y.; Sevilla, P. R.; Bettinelli, M.; Choudhury, D.; Kar, A. K.; et al. (Small, 2013)

(untitled) - Stoll, T.; Maioli, P.; Crut, A.; Rodal-Cedeira, S.; Pastoriza-Santos, I.; Vallée, F.; Del Fatti, N. (J. Phys. Chem. C, 2015)

(untitled) - Vetrone, F.; Naccache, R.; Zamarrón, A.; Juarranz de la Fuente, A.; Sanz-Rodríguez, F.; Martinez Maestro, L.; Martín Rodriguez, E.; Jaque, D.; García Solé, J.; Capobianco, J. A. (ACS Nano, 2010)

(untitled) - Kang, K.; Ozel, T.; Cahill, D. G.; Shim, M. (Nano Lett., 2008)

(untitled) - Zheng, X.; Cahill, D. G.; Weaver, R.; Zhao, J.-C. (J. Appl. Phys., 2008)

(untitled) - Wilhelm, S. (ACS Nano, 2017)

(untitled) - Balabhadra, S.; Debasu, M. L.; Brites, C. D. S.; Ferreira, R. A. S.; Carlos, L. D. (J. Phys. Chem. C, 2017)

(untitled) - Alaulamie, A. A.; Baral, S.; Johnson, S. C.; Richardson, H. H. (Small, 2017)

(untitled) - Alkahtani, M. H.; Gomes, C. L.; Hemmer, P. R. (Opt. Lett., 2017)

(untitled) - Yang, S.; Wang, Y.; Sun, H. (Adv. Opt. Mater., 2015)

Ljubljana Seminar - Gomilšek, M. (Whispering gallery modes, 2011)

(untitled) - Fernández de la Mora, J. (Annu. Rev. Fluid Mech., 2007)

(untitled) - Pustovalov, V. K. (Chem. Phys., 2005)

(untitled) - Pustovalov, V. K. (Laser Phys. Lett., 2005)